Role of LPA and the Hippo pathway on apoptosis in salivary gland epithelial cells - Hwang, Sung-Min (Exp Mol Med, 2014)
Lysophosphatidic acid (LPA) is a bioactive lysophospholipid involved in numerous physiological responses. However, the expression of LPA receptors and the role of the Hippo signaling pathway in epithelial cells have remained elusive. In this experiment, we studied the functional expression of LPA receptors and the associated signaling pathway using reverse transcriptase–PCR, microspectrofluorimetry, western blotting and immunocytochemistry in salivary gland epithelial cells. We found that LPA receptors are functionally expressed and involved in activating the Hippo pathway mediated by YAP/TAZ through Lats/Mob1 and RhoA/ROCK. Upregulation of YAP/TAZ-dependent target genes, including CTGF, ANKRD1 and CYR61, has also been observed in LPA-treated cells. In addition, based on data suggesting that tumor necrosis factor (TNF)-α induces cell apoptosis, LPA upregulates TNF-induced caspase-3 and cleaved Poly(ADP-ribose)polymerase (PARP). However, small interfering RNA treatment to Yes-associated protein (YAP) or transcriptional co-activator with a PDZ-binding motif (TAZ) significantly decreased TNF-α- and LPA-induced apoptosis, suggesting that YAP and TAZ modulate the apoptotic pathway in salivary epithelial cells.